Towards a wireless micropackaged implant with hermeticity monitoring - Jaccottet,A; Feng,P; Szostak-Lipowicz,KM; Keeble,L; Constandinou,TG (2022)
The development of reliable hermetic chip-scale micropackaging is one of the major challenges in the miniaturization of implantable medical devices. Protecting the patient from the implanted foreign body and the implant itself from the biological environment is crucial. This paper presents an implantable micropackaging concept to protect a microelectronic system-on-chip. A hermetic chamber is formed by bonding the active CMOS chip to a silicon cover using a gold-tin eutectic sealant. The cover's fabrication method and the die's post-processing steps are presented. A humidity sensor inside the chamber monitors the humidity to assess permeability. To power the sensor and read its data, interconnections in the CMOS chip have been designed; these metal tracks pass underneath the cover and thus create a connection between the inside and the outside of the cavity. As an alternative to these connections, an on-chip wireless power management and data communication system is presented with simulated results.